(untitled) (Progressive Agriculture, 2015)
The study was carried out to assess the water quality of the Jamuna river affected by effluents discharged from the nearby Jamuna Fertilizer Company Limited and its temporal change over wet and dry seasons due to change of the physico-chemical parameters. Effluents of the factories and water samples were collected from four different selected stations during the period of June to August 2014 and January to March 2015.The results further revealed that the water samples showed a remarkable variation in physico-chemical parameters during the wet and dry season. In wet season the mean value of temperature, pH, EC, TDS, TSS, DO, BOD, ammonium, nitrite, nitrate and chloride were28.63± 3.79 °C, 8.10± 0.85, 664.41± 599.54µscm-1, 370.91± 111.38 ppm, 74.49± 25.90 ppm, 6.11 ± 1.28 ppm, 75.39 ± 140.86 ppm 296.74± 303.03 ppm, 12.31±21.38 ppm, 15.19±24.49 ppm and 15.23±8.72 ppm, respectively In the dry season the mean value of temperature, pH, EC, TDS, TSS, DO, BOD, ammonium, nitrite, nitrate and chloride were31.69 ±3.18°C, 8.44± 0.66, 786.25±551.18µscm1, 338.37± 94.70 ppm, 72.08± 58.83 ppm, 5.45 ± 0.95 ppm, 86.93 ± 159.82 ppm, 347.91± 291.60 ppm, 13.68±23.1 ppm, 18.34± 24.92 ppm and 18.3±9.32 ppm, respectively. The comparative study showed that most of the effluent and water quality parameters were higher in dry season than those of the wet season because in dry season less quantity of water remains in the river and in wet season more water remains in river that has great dilution capacity. For existence and conservation of aquatic resources, it is essential to investigate the water quality and surrounding environment of the river. Progressive Agriculture 26 (2): 136-146, 2015